Kepribadian dalam Al-Qur'an dan Implikasinya dalam Pendidikan (Studi terhadap QS. Al-Baqarah: 2-20) - Parjuangan Parjuangan (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2017)
This review has been background due to a plenty of moral destruction among society. This increasingly uncontrollable promiscuity has become very common behavior in society. In fact, almost all the time a lot of negative information has been customary content served by mass media both electronics and printed ones. Even more concerning is that it has penetrated the world of education. Children of the nation who still study at school not only become victims of addicts, but they actually involved also as well as being the real player. This condition not only unsettles the parents, the teachers and the community, but also disrupts the government. But strangely, until this moment the problem still carries on and has not been resolved clearly. The purpose of this study is to know or reveal the human personality contained in the Qur'an, especially QS. Al-Baqarah: 2-20 and its implications in education. After the research, the results obtained are that every human personality is different each other, there is a personality devout belivers, disobedient belevers and also hypocritical person. This personality differences are actually found also in the world of education. School in this case the board of teachers as a substitute parents to be the most responsible component to develop students’ personality into better ones.